Identifying the impact of posted speed limits on vehicle travel mode on urban routes - Riabushenko, Oleksandr; Nahliuk, Ivan; Danets, Serhii; Bahlai, Mykola (Eastern-European Journal of Enterprise Technologies, 2025)
The object of the study is the vehicle driving mode and the results of trip on the road network of a large city under various speed limit conditions. The problem of quantitative assessment of the impact of speed limits on the average speed on the route, as well as on the indicators of driving mode unevenness, was solved. The values of such traffic parameters as average speed, average speed deviation, acceleration noise, speed gradient, energy gradient at different values of the posted speed limit (PSL) were obtained. Graphs of changes in the average speed and indicators of the unevenness of the speed regime were constructed and mathematical models of the dependence of the average speed on urban routes on the adopted speed limit were proposed. The results showed an increase in the average speed on the route by an average of 2.4 km/h with an increase in PSL by 10 km/h. At the same time, the dependence of the average speed on the PSL is non-linear and shows a decrease in the impact of the speed limit factor at higher PSL values (from 3.5 km/h for a PSL of 50 km/h to 1.24 km/h for a PSL of 80 km/h). Increasing the PSL does not affect the specific time in motion and leads to an increase in the specific idle time. With an increase in PSL, the acceleration noise and energy gradient increase. The increase in average speed is explained by the ability to increase speed in low-loaded sections of the route, but with an increase in PSL, the ability to realize the increased speed decreases, and the traffic mode itself becomes more uneven. The research was carried out using the “driving laboratory” method on three different routes under the same initial conditions for speed limits from 50 to 80 km/h. The driving mode of the car was recorded in the form of GPS tracks. The results can be used to assess the impact of PSL changes on the technical and economic performance of urban road transport. The results will also be useful in conducting an information campaign and promoting a culture of compliance with the speed limits established in cities among drivers